Candidate Regulatory Elements in Coding and Noncoding Regions are Associated With Invasive Behavior in Pituitary Tumors. (1st September 2019) - Asmaro, Karam P; Mosella, Maritza S; Wells, Michael; Sabedot, Thais; Malta, Tathiane; Nelson, Kevin; Snyder, James; DeCarvalho, Ana; Mukherjee, Abir; Chitale, Dhananjay; Aho, Todd; Robin, Adam M; et al.
Abstract: INTRODUCTION: Unique genome-wide DNA methylation patterns have been shown to define pituitary tumors (PT) by functional subtypes and play a relevant role in the pathogenesis of these tumors. Indeed, it is known that several tumor suppressor genes involved in the pituitary tumorigenesis are rarely inactivated by mutations but by hypermethylation of their promoters. DNA methylome modifications in regulatory regions outside of promoter regions and their influence on invasive behavior is less clear. We hypothesized that DNA methylation abnormalities in regulatory genomic elements, specifically in enhancers, are associated with invasive behavior in pituitary macroadenomas. METHODS: We compiled and analyzed publicly available and in-house generated genome-wide methylome profiles (Illumina 450 K or 850 K/EPIC platforms) across 32 invasive and 35 noninvasive PT and performed a comprehensive and integrative analysis in an available matching methylome and RNA-seq subset of patients. RESULTS: Comprehensive and integrative analysis of epigenomic and transcriptomic data from the PT cohort revealed that differentially methylated regions (DMR) in invasive macroadenomas were mainly hypomethylated in relation to their noninvasive counterparts. These hypomethylated probes were enriched for enhancers mainly located in noncoding regions. In addition, the nearest genes related to enhancers annotated in coding regions were associated with pathways mainly involved in regulation of membrane potential and signaling by receptor of tyrosine kinase (RTK). Integration of the DMR and gene expression revealed novel deregulated genes in PT such as Inositol-Trisphosphate 3-Kinase B (ITPKB). CONCLUSION: This study revealed previously unappreciated hypomethylation of key regulatory elements, annotated in candidate enhancer regions. These findings refine our understanding of the epigenomic complexity that drives the invasive behavior of pituitary macroadenomas. The gene specific expression identified can aid in providing future actionable pathways (eg, signaling of receptor of tyrosine kinase) to provide adjuvant therapies and precision medicine.